Does Climate Change Make Foodgrain Yields More Unpredictable? Evidence from India - Saumya Verma; Shreekant Gupta; Partha Sen (Center for Economic Studies and ifo Institute (CESifo), 2020)
How would climate change affect India's agriculture which accounts for sixty percent of employment? We study the impact of climate change on the level and variability of yields of rice (India's major food crop) and two key millet crops (sorghum and pearl millet), using an all India district level panel dataset from 1966-2011. A stochastic production function is estimated with exogenous climate anomalies. We find that climate change adversely affects both the level and variability of crop yields - rice yields are reduced by rainfall extremes whereas extremely high temperatures make yields of all three crops highly variable with the biggest impact on millets.
Keywords: Q54; O13; D24; 330; agriculture; climate change; foodgrain yields; India; millets; rice; stochastic production function